2018
DOI: 10.1038/s41467-018-03616-y
|View full text |Cite
|
Sign up to set email alerts
|

GS9 acts as a transcriptional activator to regulate rice grain shape and appearance quality

Abstract: Identification of grain shape determining genes can facilitate breeding of rice cultivars with optimal grain shape and appearance quality. Here, we identify GS9 (Grain Shape Gene on Chromosome 9) gene by map-based cloning. The gs9 null mutant has slender grains, while overexpression GS9 results in round grains. GS9 encodes a protein without known conserved functional domain. It regulates grain shape by altering cell division. The interaction of GS9 and ovate family proteins OsOFP14 and OsOFP8 is modulated by O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
172
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(172 citation statements)
references
References 55 publications
0
172
0
Order By: Relevance
“…The selection to GLA vgl is beneficial to rice quality improvement Grain length is closely related to grain quality (Zhao et al, 2018). We evaluated the grain quality of NILs and found that rice milled from NIL-GLA had high percentages of chalky grain and chalky area with loose and irregular starch granules, unlike that from NIL-gla, which displayed compactly arranged and largely sharpedged polygonal starch granules (Figure 7a-d).…”
Section: Phenotypic Characterization Of Nil-gla and Nil-glamentioning
confidence: 99%
“…The selection to GLA vgl is beneficial to rice quality improvement Grain length is closely related to grain quality (Zhao et al, 2018). We evaluated the grain quality of NILs and found that rice milled from NIL-GLA had high percentages of chalky grain and chalky area with loose and irregular starch granules, unlike that from NIL-gla, which displayed compactly arranged and largely sharpedged polygonal starch granules (Figure 7a-d).…”
Section: Phenotypic Characterization Of Nil-gla and Nil-glamentioning
confidence: 99%
“…GRAIN LENGTH AND WEIGHT ON CHROMOSOME7 ( GLW7 ) and GW8 encode SQUAMOSA promoter‐binding protein‐like transcription factors that positively regulate seed size by promoting cell elongation or division (Wang et al 2012; Si et al 2016). GRAIN SHAPE GENE ON CHROMOSOME9 ( GS9 ) encodes a transcriptional activator involved in the regulation of grain shape by altering cell division (Zhao et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Grain size is an important and complex agronomic trait that determines yield potential and is controlled by polygenes. A number of major quantitative trait loci (QTLs) controlling grain size have been successfully isolated and characterized, such as GS3 (Fan et al ., ; Mao et al ., ), GS5 (Li et al ., ), GS9 (Zhao et al ., ), GW2 (Song et al ., ), GW5 (Shomura et al ., ; Weng et al ., ), GW7 (Wang et al ., ), GW8 (Wang et al ., ) and TGW6 (Ishimaru et al ., ). Furthermore, recent studies have revealed that a number of transcription factors act as key grain size regulators.…”
Section: Introductionmentioning
confidence: 99%